Using isotopic dilution to assess chemical extraction of labile Ni, Cu, Zn, Cd and Pb in soils. (July 2016) - Garforth, J.M.; Bailey, E.H.; Tye, A.M.; Young, S.D.; Lofts, S.
Abstract: Chemical extractants used to measure labile soil metal must ideally select for and solubilise the labile fraction, with minimal solubilisation of non-labile metal. We assessed four extractants (0.43 M HNO3, 0.43 M CH3 COOH, 0.05 M Na2 H2 EDTA and 1 M CaCl2 ) against these requirements. For soils contaminated by contrasting sources, we compared isotopically exchangeable Ni, Cu, Zn, Cd and Pb (EValue, mg kg −1 ), with the concentrations of metal solubilised by the chemical extractants (MExt, mg kg −1 ). Crucially, we also determined isotopically exchangeable metal in the soil–extractant systems (EExt, mg kg −1 ). Thus 'EExt – EValue ' quantifies the concentration of mobilised non-labile metal, while 'EExt – MExt ' represents adsorbed labile metal in the presence of the extractant. Extraction with CaCl2 consistently underestimated EValue for Ni, Cu, Zn and Pb, while providing a reasonable estimate of EValue for Cd. In contrast, extraction with HNO3 both consistently mobilised non-labile metal and overestimated the EValue . Extraction with CH3 COOH appeared to provide a good estimate of EValue for Cd; however, this was the net outcome of incomplete solubilisation of labile metal, and concurrent mobilisation of non-labile metal by the extractant (MExt  < EExt  > EValue ). The Na2 H2 EDTA extractant mobilised some non-labile metal in three of the four soils, but consistently solubilised the entire labile fraction for all soil-metal combinations (MExt  ≈ EExt ). Comparison of EValue, MExt and EExt provides a rigorous means of assessing the underlying action of soil chemical extraction methods and could be used to refine long-standing soil extraction methodologies. Highlights: Stable isotope dilution can inform underlying mechanisms during chemical extraction. Agreement between extracted metal and E values is sometimes fortuitous. Powerful extractants (0.05 M EDTA and 0.43 M Nitric acid) solubilise non-labile metal. Weaker extractants (0.43 M CH3 COOH and 1 M CaCl2 ) fail to solubilise all labile metal. E values measured within on the soil extraction reveal non-labile metal mobilisation.